Oat cultivars developed at Nemchinovka and included into the State Register in recent years (a review) - A. D. Kabashov; I. G. Loskutov; N. M. Vlasenko; Ya. G. Leibovich; A. S. Markova; Z. V. Filonenko; L. G. Razumovskaya (Труды по прикладной ботанике, генетике и селекции)
The main trend in crop breeding is to increase productivity and improve grain quality indicators. The formation of high crop productivity requires cultivars with high potential for productivity and quality as well as with resistance to biotic and abiotic environmental factors. Successful solution of these and emerging breeding problems is possible only if appropriate source material is employed.Source material from the Vavilov Institute’s collection of plant genetic resources was used in crosses aimed at the development of oat cultivars. Its brief description is presented here.The results of the breeding work on oat cultivars at the Nemchinovka Federal Research Center from 2007 through 2017 are discussed. Descriptions are given to all ten developed oat cultivars with a detailed pedigree for each combination of crosses. Pedigree analysis has been performed, and its results show a limited number of parental forms for crosses. The problem of source material utilization in breeding practice and narrowing of the genetic base in the process of cultivar development is discussed.